Analysis of Hepatobiliary Disorder Reports Associated With the Use of Herbal Medicines in the Global Suspected ADR Database Vigibase - van Hunsel, Florence; van de Koppel, Sonja; Skalli, Souad; Kuemmerle, Andrea; Teng, Lida; Wang, Jia-bo; Barnes, Joanne (Frontiers in Pharmacology, 2019)
Introduction Use of herbal medicines (HMs) is widespread across the world, with many people relying on HMs for their primary healthcare or using HMs in the context of a healthy life style. HMs originate from plant material and, as such, are often seen as ‘natural’ and believed to be (relatively) safe by patients. Hepatobiliary disorders have been associated with numerous HMs. Aim This paper aims to analyze reporting patterns for hepatobiliary disorders associated with HMs use from reports submitted to the WHO global database of individual case safety reports (ICSRs) VigiBase. Methods A data extraction in VigiBase, the WHO international database of ICSR reports, was performed by the Uppsala Monitoring Centre on 2019-01-16. The dataset contained all ICSRs where an HM was identified with the UMC-assigned ATC code ‘V90: unspecified herbal and traditional medicine’ and where the HM was classified as being either the suspected drug or an interacting drug, and containing at least one adverse reaction in the MedDRA® System Organ Class (SOC) Hepatobiliary Disorders (HBD). Descriptive analyses in Excel 2013® were used to determine general characteristics of the reports in the broad data set, including total number of reports, reporting country and patient characteristics. For single suspect herbal reports, reports categorized as ‘serious’ were extracted. Results In total, 2483 reports describing with at least one ADR in the SOC HBD were extracted from VigiBase. In total, 780 (31.4%) reports concern only one suspect HM. However, for 188 reports of these reports (24.1%), the single suspect herbal preparation contains more than one herbal ingredient. The 592 reports for single suspect herbal preparations described a total of 764 ADRs in the SOC HBD. Jaundice was the most reported ADR for these reports. Conclusion Almost 2500 reports for HMs and with at least one ADR coded to the MedDRA® SOC HBD were retrieved from VigiBase. Of the HBD SOC HM reports, around 25% concerned a single herbal species as the suspect ‘drug’. Substantial issues with coding of the suspect herbal drugs were found. In-depth causality assessment of the cases is needed to draw conclusions on the strength of the relationships.